Levels of depression and anxiety in university students in Lima metropolitana - Riveros Q., Marcelino (2007)
In this investigation we display the level of anxiety and depression in university students of the UNMSM. The representative sample was formed by 500 university students of the UNMSM, distributed by sort and by academic block, in which we evaluated prevalence of depression and anxiety by means of denominated test HADS, constituted by seven items for each upheaval, with a pentane from 0 to 3, translated into Spanish. Since this test has been used in North America and Asian countries, it was assumed that there is already an international tendency. In Lima do not exist works with the HADS.